Antagonism of 5-hydroxykynurenamine against serotonin action on platelet aggregation. - Okuma, M (1976)
Serotonin induced an aggregation of human platelets, whereas 5-hydroxykynurenamine, produced from serotonin by the action of indoleamine 2,3-dioxygenase, did not cause any significant degree of platelet aggregation. 5-Hydroxykynurenamine specifically inhibited both a serotonin-induced aggregation of platelets and the potentiation of the ADP-induced platelet aggregation by serotonin. It did not, however, alter the profiles of the platelet aggregation induced by ADP, collagen, or adrenaline. The degree of inhibition was proportional to the time of preincubation of platelets with 5-hydroxykynurenamine, and to the concentration of 5-hydroxykynurenamine used. Available evidence indicated that 5-hydroxykynurenamine completed with serotonin for the same receptor sites. Studies with analogues of 5-hydroxykynurenamine indicated that the substitutions of 0-amino-benzyl moiety with hydroxy or methoxy groups were somewhat tolerated, whereas the masking of alkylamine moiety with N-acetylation completely lost the inhibitory activity.